Parent-Child Relationship of Pedometer-Assessed Physical Activity and Proxy-Reported Screen Time in Czech Families with Preschoolers - Sigmund, Erik; Badura, Petr; Vokacova, Jana; Sigmundová, Dagmar (International journal of environmental research and public health, 2016)
This study focuses on determining the relationship between parents' step count (SC) and screen time (ST) and children's SC and ST on weekdays and at weekends. The participants (278 parents aged 30-45 and their 194 children aged 4-7) were recruited from 10 randomly selected Czech kindergartens. The participants recorded SC and ST duration over a week-long monitoring (≥8 h/day) during September-October 2014 and April-May 2015. The associations between parents' SC and ST and children's SC and ST were estimated using general linear regression for weekdays and weekends. Each 2500 SC increase in mothers'/fathers' daily SC at weekdays (weekends) was associated with an extra 1143/903 (928/753) daily SC in children. Each 60 min of ST increase in mothers'/fathers' ST at weekdays (weekends) was associated with an extra 7.6/7.6 (16.8/13.0) min of child daily ST. An increase of 2500 mothers' daily SC was associated with reduction of 2.5 (7.5) min of ST in children at weekdays (weekends). This study reveals a significant relationship between parent-child SC/day, parent-child ST/day, and mothers' ST and children's SC at weekends. Weekend days seem to provide a suitable space for the promotion of joint physical activity in parents and their pre-schoolers.
Keywords: aktigrafie; dospělí; Sedentary Behavior; Female; dítě; předškolní dítě; Television; Adult; Linear Models; sedavý životní styl; ženské pohlaví; vztahy mezi rodiči a dětmi; lidé; Yamax pedometer; step count; cvičení; školy; rodiče; lineární modely; Computers; Schools; otcové; Parents; Actigraphy; weekends; matky; Male; televize; Czech Republic; Mothers; Parent-Child Relations; Child, Preschool; Česká republika; lidé středního věku; Child; Fathers; počítače; fathers; mužské pohlaví; screen time; Exercise; mothers; weekdays; Middle Aged; Humans